Cydnidae (burrowing bug) pigmentation in a 6-month-old baby. - S, Soundarya; Sabapathi, Vaishnavi; Thomas , Jayakar (European Journal of Pediatric Dermatology, 2022)
Cydnidae insects belong to the superfamily Pentatomoidea, family Cydnidae, order Hemiptera and suborder Heteroptera (8). These insects have a flattened head with a dark brown or black ovoid body measuring approximately 2-20 mm in diameter, with thorny legs that feature significant variations in the tibia and tarsus: these anatomical variations help them deftly dig underground and feed on the roots of plants (hence the name of burrowing bugs). They breed mainly in the monsoon or rainy season. They have a life cycle of 100-300 days […].